Therapie des zerebral metastasierten, HER2-positiven Mammakarzinoms (Deutsche Zeitschrift für Onkologie, 2020)
Gori S et al. The HERBA Study: A retrospective multi-institutional Italian study on patients with brain metastases from HER2-positive breast cancer. Clin Breast Cancer 2019; 19: e501–e510. doi: 10.1016/j.clbc.2019.05.006